THE COMPARISON OF BANKING SUPERVISION MODEL IN INDONESIA, UNITED KINGDOM, SOUTH KOREA AS EFORTS TO IMPROVE INDONESIAN SUPERVISION SYSTEM - Sulistyandari Sulistyandari (Jurnal Dinamika Hukum, 2015)
This study aims to improve banking supervision by conductingcomparative studies research model of banking supervision in Indonesia, the UK, South Korea and the aspirations of the respondents (Bank, OJK, theorist) in Central Java on efforts to improve banking supervision is now done in Indonesia. The results show Indonesian comparison with the UK and South Korea gives the idea that the OJK in charge of education and consumer protection to enhance its role as practiced by the FCA in the UK, and the LPS assignments need to be expanded in order to ensure that all consumers of financial institutions as was done by the FSCS in the UK and KDIC in South Korea. Aspirations of the people of the regulation and supervision of banking include aspects of regulatory, law enforcement, infrastructure, community (the Bank) and culture.Keywords: comparison of banking supervision.